Socio-economic Identification Post Rob Flood in the Romantic Beach Area of Sei Naga Lawan Perbaungan District Serdang Bedagai District - Susilawati, Susilawati; Rangkuty, Meisa Putri; Asti, Rahma Dwi; Dalimunthe, Nadiyah Rahma; Br. Ginting, Radha Agri (Universitas Ibn Khaldun Bogor, 2025)
In Indonesia’s coastal areas, especially along the North coast of Java, tidal floods are a significant natural disaster threat. This disaster had a serious impact on environmental conditions and resulted in changes in the social and economic order of local communities. A study was conducted to assess the social and economic impacts of tidal flooding on Romantis Beach which is located in Sei Naga Lawan Village, Perbaungan District, Serdang Bedagai Regency. This research aims to identify economic and social impacts on society, as well as analyze mitigation efforts carried out by the government. The research uses a qualitative descriptive approach by collecting data through in-depth interviews. Resource persons include local government officials, affected residents, and communities who have lived in the Romantis Beach area for at least five years. Research findings reveal a significant decline in people’s income, especially those who depend on the fisheries and tourism sectors for their living. Daily income, which previously reached IDR 500,000, decreased to IDR 300,000 after the tidal flood. This condition forces some residents to change professions to survive.From a social aspect, there was no conflict found in society. On the contrary, this disaster actually strengthened community solidarity in recovery efforts. Even though long-term mitigation efforts such as the construction of wave breakers have been hampered due to limited funds, the community remains united in restoring conditions. The local government contributes by building green open spaces as water catchment areas. To increase community resilience, greater attention is needed from various par’ies including the government, NGOs and the private sector in supporting long-term economic recovery and infrastructure development programs.